Device Longevity in a Contemporary Cohort of ICD/CRT‐D Patients Undergoing Device Replacement. (17th June 2016) - ZANON, FRANCESCO; MARTIGNANI, CRISTIAN; AMMENDOLA, ERNESTO; MENARDI, ENDRJ; NARDUCCI, MARIA LUCIA; DE FILIPPO, PAOLO; SANTAMARIA, MATTEO; CAMPANA, ANDREA; STABILE, GIUSEPPE; POTENZA, DOMENICO ROSARIO; PASTORE, GIANNI; IORI, MATTEO; et al.
Longevity of Replaced ICD/CRT‐D: Introduction: The longevity of defibrillators (ICD) is extremely important from both a clinical and economic perspective. We studied the reasons for device replacement, the longevity of removed ICD, and the existence of possible factors associated with shorter service life. Methods and Results: Consecutive patients who underwent ICD replacement from March 2013 to May 2015 in 36 Italian centers were included in this analysis. Data on replaced devices were collected. A total of 953 patients were included in this analysis. In 813 (85%) patients the reason for replacement was battery depletion, while 88 (9%) devices were removed for clinical reasons and the remaining 52 because of system failure (i.e., lead or ICD generator failure or a safety advisory indication). The median service life was 5.9 years (25th–75th percentile, 4.9–6.9) for single‐ and dual‐chamber ICD and 4.9 years (25th–75th percentile, 4.0–5.7) for CRT‐D. On multivariate analysis, the factors CRT‐D device, SC/DC ICD generator from Biotronik, percentage of ventricular pacing, and the occurrence of a system failure were positively associated with a replacement procedure. By contrast, the device from Boston Scientific was an independent protective factor against replacement. Considerable differences were seen in battery duration in both ICD and CRT‐D. Specifically, Biotronik devices showed the shortest longevity among ICD and Boston Scientific showed the longest longevity among CRT‐D (log‐rank test, P < 0.001 for pairwise comparisons). Conclusion: Several factors were associated with shorter service life of ICD devices: CRT‐D, occurrence of system failure and percentage of ventricular pacing. Our results confirmed significant differences among manufacturers.